Enhancing digital information access in public libraries - Ayers, Kathleen; Liu, Yan Quan (Proceedings of The Asist Annual Meeting, 2007)
Purpose To explore the impact of public digital library resources on urban residents, to elucidate the current usage patterns of public digital library resources/services and levels of satisfaction with the resources/content in urban digital libraries and make recommendations as to steps that would improve service to this population. Design/Methodology/Approach We conducted an anonymous user-completed survey study of 6 urban libraries to collect demographic and information regarding satisfaction with Digital Library (DL) resource and patterns of use. Findings Our respondents represented a cross section of races, genders, ages, and educational backgrounds. Our results in this much-needed area of study demonstrate that libraries should plan to provide more access, less filtering, regular upgrades, and more training to use the resources. Practical Limitations/Implications Larger studies should be used to follow up this report, in order to be able to obtain a generalized understanding of overall patterns of urban residents using DLs in public settings. Recruitment techniques did not adequately sample potential (but not current) DL users. Originality/Value This study contributes to a scant empirical data set addressing the impact that access to public digital information and services have on urban residents. We offer new data and recommendations that will guide public library administrators in enhancing the impact, efficiency and value of public DL resources/services to improve the digital learning environment for life-long educaiton at all levels in a broad community of urban users.
0 citations (Crossref) [2023-10-31] tex.ids: lens.org/027-715-068-622-316 tex.type: [object Object]
Keywords: dept.ils; ⛔ No DOI found

Developing an integrated public library service in Dongguan, one of China's fastest growing cities - Liu, Yan Quan; Li, Donglai (New Library World, 2007)
Purpose - The purpose of this case study is to explore the construction pattern and issues involved in the development of an urban library service system in China. Design/methodology/approach - This study was conducted through an analytical evaluation of the development of an integrated public service system and its distribution of information among libraries and information centers in an urban community. Findings - Constructing an integrated public service system is an important trend in urban libraries in the new millennium. Drawing from the Dongguan library's integrated public service system that aims to master better various resources from whole service area, this text summarizes technology innovation and the significant results of the Dongguan library system redevelopment, providing an absorbing insight into developments in the Chinese public library service. Originality/value - While the ultimate goal of integration is to provide better services to meet the information-seeking needs of urban residents, it is necessary to meet these needs through a technological breakthrough in the administration of clustered libraries, to instill a central branch system, and to work out the advantages of group service.
0 citations (Crossref) [2023-10-31] tex.ids: lens.org/074-087-094-612-648 tex.type: [object Object]
Keywords: China; Digital libraries; Library management Public sector organizations; Public libraries; dept.ils